Gereja Yang Bermisi Bagi Kaum Perempuan di Era Post Modern - Goha, Freis (Program Studi Misiologi dan Komunikasi Kristen, 2024)
The postmodern era presents challenges as well as opportunities for the church in carrying out relevant missions, especially for women. This article aims to explore how the church can become an agent of social transformation that is inclusive and responsive to women's needs amidst the dynamics of postmodern culture. This research uses qualitative methods with a theological approach and social analysis, including literature study. The main results of the research show that churches that implement a holistic approach, such as empowering theological education, community-based service programs, and social justice advocacy, are able to increase gender awareness and women's participation in church life and wider society. The main conclusion confirms that a church with a mission for women not only fulfills the call of faith, but also becomes a witness to God's love and justice in an ever-changing world. The Church needs to continue to adapt its mission strategy to remain relevant and impactful in facing the challenges of the postmodern era